The Role of Human Resource Competence and Entrepreneurial Motivation on the Performance of Women Entrepreneurs - Juniarta, I; Merta, I; Ardiansyah, Wisnu (Jurnal Ilmiah Manajemen Kesatuan, 2023)
This research aims to investigate the impact of human resource competence and entrepreneurial motivation on the performance of women entrepreneurs in the fashion industry of Klungkung Regency, Bali, Indonesia, specifically within micro, small and medium enterprises (MSMEs). The study draws upon management theory, middle-range human resource theory, and applied theories related to human resource competence, motivation, and entrepreneurship. The research methodology employed is quantitative, using questionnaires as the primary data collection tool. The study involves a sample of 54 SME businesses, and data analysis is conducted using SPSS software version 24. Three hypotheses were tested in this research. The results indicate that the variable of human resource competence has a significant positive influence on entrepreneurial performance. Furthermore, human resource competence also has a significant positive effect on entrepreneurial motivation. The variable of entrepreneurial motivation also significantly influences entrepreneurial performance. However, it is noteworthy that the impact of human resource competence and entrepreneurial motivation on entrepreneurial performance is considered relatively modest. Keywords: Entrepreneur Performance, HR Competence, Entrepreneurial Motivation, Women Entrepreneurs, Fashion Industry. ABSTRAK Penelitian ini bertujuan untuk menyelidiki dampak kompetensi sumber daya manusia dan motivasi berwirausaha terhadap kinerja para pengusaha wanita di industri fashion Kabupaten Klungkung, Bali, Indonesia, khususnya dalam usaha mikro, kecil, dan menengah (UMKM). Studi ini mengacu pada teori manajemen, teori sumber daya manusia tingkat menengah, dan teori terapan terkait kompetensi sumber daya manusia, motivasi, dan kewirausahaan. Metodologi penelitian yang digunakan bersifat kuantitatif, dengan menggunakan kuesioner sebagai alat pengumpulan data utama. Studi ini melibatkan sampel dari 54 usaha UMKM, dan analisis data dilakukan menggunakan perangkat lunak SPSS versi 24. Tiga hipotesis diuji dalam penelitian ini. Hasil penelitian menunjukkan bahwa variabel kompetensi sumber daya manusia memiliki pengaruh positif yang signifikan terhadap kinerja berwirausaha. Selain itu, kompetensi sumber daya manusia juga memiliki pengaruh positif yang signifikan terhadap motivasi berwirausaha. Variabel motivasi berwirausaha juga berpengaruh signifikan terhadap kinerja berwirausaha. Namun, perlu dicatat bahwa dampak kompetensi sumber daya manusia dan motivasi berwirausaha terhadap kinerja berwirausaha dianggap relatif sederhana Kata kunci: Kinerja Berwirausaha, Kompetensi SDM, Motivasi Berwirausaha, Pengusaha Wanita, Industri Fashion